MENTORING KADER POSYANDU UNTUK MENINGKATKAN KETERAMPILAN DALAM MENGINPUT DATA KIA BERBASIS ANDROID - Elais Retnowati (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2019)
The Posyandu has a website to collect data on Maternal and Child Health (MCH) and the Posyandu cadre is tasked with inputting data into the web, but not all cadres can do the task because they do not master information technology (IT).This research method using quasi experiment. Result showed cadre performance on inputing MCH data increase from 3 become 7 document in 15 minute. This article describes a way to overcome the problem of inputting MCH data using an Android-based mobile phone. This article on mentoring practices illustrates how android technology can be used by cadres in inputting data that can be done at any opportunity. The facilitators input MCH data through android not only to make cadres recognize the technology that is close to themselves but also improve their performance in inputting MCH data.